Exposure to 27 polychlorinated biphenyls in the indoor environment of a workplace: a controlled bio-monitoring study - Pedersen, Ellen Botker; Ebbehoj, N. E.; Göen, Thomas; Meyer, H. W.; Jacobsen, P. (International Archives of Occupational and Environmental Health, 2016)
To assess the exposure to a broad-spectrum of polychlorinated biphenyl congeners (PCBs) from the indoor environment through bio-monitoring of people working in a building with PCB-containing materials and elevated PCB levels in the indoor air.A cross-sectional study comparing the plasma concentration of 27 PCB congeners in 15 people working in a PCB-contaminated building and 30 matched controls.Median concentration of eight low-chlorinated PCB congeners was significantly higher in the exposed than in the control group. The sum of median concentrations of tri + tetra-chlorinated PCB was almost ten times higher in the exposed group than in the unexposed, and sums of dioxin-like and non-dioxin-like PCB were both relatively increased by 60 % in the exposed group.The occupational indoor environment may significantly add to PCB exposure, especially to the lower-chlorinated congeners. Health effect from this little-acknowledged exposure has not yet been documented, but data supporting lack of effect are sparse and research generating information on effect of exposure to specific congeners including at levels relevant for the indoor environment should be encouraged.
EVALuna2:9742